The Great War : Insights and Perspectives - Dzikowska, Elżbieta Katarzyna 1950- (Geschichte – Erinnerung – Politik. Studies in History, Memory and Politics, 2016)
This publication is a collection of articles which summarise results of investigations into archival materials concerning wartime stories of various nations involved in the Great War. The objective of the authors was to analyse the wartime experience of individuals and local communities as well as whole nations. They further tried to present a closer, more personal overview of wartime drama. As a result the book portrays the impact of the Great War on the lives of multicultural communities, re-constructs individual war narratives and studies consequences of the conflict. The use of various types of historical materials from state archives and from other sources enabled the authors to create a multifaceted portrayal of the war seen from local and international perspectives